Performance comparison of Photovoltaic sources based multilevel inverters in smart grid - N P G, Bhavani; N, Kavitha; D, Sheela; CH, Sarada Devi; C, Prameeladevi; K, Sujatha (Devices for Integrated Circuit, 2025)
Multilevel inverters (MLIs) and photovoltaic (PV) sources in coordination improves smart grid performance. This paper evaluates the performance of PV-based MLIs in terms of efficiency, reliability, and power quality. Diode-clamped, flying capacitor, and cascaded H-bridge inverters are among the MLI topologies that are examined and contrasted under various operating circumstances. Parameters are compared to select the best suited topology for the work. To ascertain their appropriateness for smart grid applications, crucial performance indicators are evaluated, including complete distortion of harmonics, switching losses, and overall system efficiency. The impact of dynamic PV generation, grid interaction, and load variations on the inverter performance is also explored. The power conversion quality and operational stability of smart grids are greatly impacted by the MLI topology selection. This study provides insights into the optimal selection and design of PV-based MLIs to enhance the sustainability and efficiency of modern smart grid systems.